• Matéria: Matemática
  • Autor: alexdalarmi
  • Perguntado 7 anos atrás

1 - Calcule a seguinte expressão:
(+\frac{3}{4}) ^{-2}  + (-\frac{3}{4}) ^{-3}

Respostas

respondido por: dddrenel
1

Resposta:

( +  \frac{3}{4} )^{ - 2}  + ( -  \frac{3}{4} )^{3}  =  -  \frac{16}{27}  \:  = -  0.593

Explicação passo-a-passo:

( +  \frac{3}{4} )^{2}  =  \frac{16}{9}  \\  \\  \frac{16}{9}  + ( -  \frac{3}{4} ) ^{ - 3}  =  \\  \\  \frac{16}{9}  -  \frac{64}{27}  = -   \frac{16}{27}  =  - 0.593

Perguntas similares